THE IMPACT OF WORKING CAPITAL MANAGEMENT ON SME PROFITABILITY – EVIDENCE FROM KOSOVO* - Ardi Ahmeti; Yllka Ahmeti; Skender Ahmeti (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2022)
The study attempts to show the impact of working capital management on the profitability of ninety-eight Kosovo-based SMEs, primarily in the manufacturing and construction sectors. The data were obtained from the financial statements of these companies for the years 2010 through 2020, and the assumptions were verified using the Ordinary least square (OLS) method. To express SMEs profitability, return on assets (ROA) is taken as a dependent variable, while to express working capital management, independent variables are taken: the inventory turnover period (INTP), receivables collection period (TRCP), trade payable period (TPP), and cash conversion cycle (CCC). In addition, are taken four control variables (size of companies, current ratio, sustainable growth, and leverage), which are not a variable of interest in the study but could influence the outcomes. The results reveal that SMEs increase profitability by decreasing the cash INTP and increasing TRCP, TPP, and CCC. By analyzing the effect of working capital management on profitability in the context of SMEs in Kosovo, this research contributes new knowledge to the existing literature.